Development of DNA Based Technologies for Detection of Genetically Modified Organisms - Cheah, Yoke Kqueen (2006)
Genetically modified organisms (GMOs) can be defined as organisms in which the genetic material (DNA) has been altered in a way that does not occur naturally by mating, pollination or natural recombination, i.e. by being genetically modified (GM) or by recombinant DNA technology. With the introduction of foods derived from genetically modified organisms in the market, there has been an increasing need for appropriate analytical methods to comply with the strict regulations in the European Union (EU) and other regions. Raw, processed food and animal feed were the three main category of food used in this study. In addition, the matrices of food tested comprise solid, semi-solid and liquid. Thus, different DNA isolation techniques were used in this study to ensure the quality and purity of the extracted DNA. The DNA extraction techniques used in this study were based on the silica column binding and magnetic bead entrapment technology.The polymerase chain reaction (PCR) allows the millionfold amplification of a target DNA fragment in a highly sensitive and specific manner. Single specific PCR with the published and designed primers were generated. Combination of the published and new primers in PCR contributes to the development of rapid detection in GMO analyses. In real-time PCR technology, the amplification of the DNA sequence can be monitored during the whole reaction by indirect monitoring of the product formation. Real-time detection strategies rely on continuous measurements of the increments in the fluorescence generated during the PCR. The chemistries for the real-time PCR used in this study include SYBR Green I, hybridization probes (Taqman) and AmplifluorTM universal system. The SYBR Green I and the hybridization probes system used in this study was successfully optimized to detect delta endotoxin gene from Bacillus thuringiensis, (CryIA(b)), gene for 5’enol-pyruvylshikimate-3- phosphate synthase (EPSPS), species specific regions of the soybean lectin gene and the maize zein gene. On the other hand, the AmplifluorTM universal system was successfully optimized for the detection of the soybean lectin gene, Cauliflower Mosaic virus 35S promoter gene and the Roundup Ready soya specific gene. Dot blot assay provides an alternative detection method in GMO detection. Two biotinylated probes were successfully generated for the detection of transgenic food namely the detection of the 5’enol-pyruvylshikimate-3-phosphate synthase (EPSPS) gene and the Cauliflower Mosaic virus 35S promoter gene fragments. In addition, the membrane-based technique described in this study involves the use of chemiluminescent detection. Although this nonradioactive DNA probes is lower sensitivity than PCR, it is easier to process for large numbers of samples at once and inexpensive. Random amplified polymorphic DNA (RAPD) analysis used in this study was able to distinguish between commercially obtained genetically modified materials with normal food. Random primer OPAR 4 and OPAR 13 were found to discriminate the samples from standards used. The RAPD analysis introduced in this study could be used in pre-GMO food screening and genetic relatedness investigation. Besides that, the combined banding profile analysis of both OPAR4 and OPAR13 revealed better clustering of the samples tested. RAPD patterns are always species-specific and some primers produce highly polymorphic patterns within a species. Biospecific interaction analysis (BIA) via Surface Plasmon Resonance (SPR) for the detection of the lectin, CaMV 35S promoter, Nos terminator and Roundup Ready gene introduced in this study is an appropriate method for GMO detection since the techniques is label free, no toxic compounds are required, easy, rapid, specific and automatable. Since light does not penetrate the sample, interactions can be followed in colored, turbid or opaque samples. Thus, BIA via SPR is suitable for the detection of GMO especially in processed food. In this study, attempts were successfully conducted in detection of asymmetry PCR amplicons and raw DNA extracts of selected GMO products. As conclusion, all the DNA based method described in this study demonstrated fast, accurate and specific approach. Besides that, techniques such as RAPD introduced in this study can used as an investigation tools in the study of genetic relatedness between GMO and non-GMO samples. On the other hand, dot blot analysis described in this study offers an alternative inexpensive approach in preliminary detection of GMOs. Likewise, a combination of several DNA based detection method such as Real-time PCR (SYBR Green I, hybridization probes (Taqman) and AmplifluorTM universal system) and SPR biosensor will ensure reliable and reproducible results.